Pendampingan Pembuatan Metode Pembayaran Quick Response Code Indonesian Standard (QRIS) Pada UMKM dan Rumah Ibadah di Desa Balapulang Wetan - Aminulloh, Wasis; Nabiyi, Ihda Oktavian; Azzam, Abdullah; Mas’udip, Ali; Febrianti, Andin; Sonia, Jihan; ’Afita, Luthfatul Laeli Nur; Apriliaji, Heru; Faizin, Ahmad Nur (Lembaga Penelitian, Penerbitan, dan Pengabdian Masyarakat, 2025)
This research examines the implementation of assistance in the use of digital payment methods through the Quick Response Code Indonesian Standard (QRIS) for MSMEs and houses of worship in Balapulang Wetan Village as an effort to support digital transformation in the financial system. Using a Participatory Action Research (PAR) approach, this activity involves the active participation of MSME players (Wedding Decoration MSME and Embroidery MSME) and the manager of houses of worship (Majlis Saung Sholawat) through the stages of needs survey, discussion forums, training, and implementation assistance. Socialization and education about the benefits, registration procedures, and use of QRIS have succeeded in increasing digital literacy and participants' confidence in non-cash transactions. Evaluation results show that QRIS has been well implemented, accelerates transactions, increases payment security, and supports transparency of financial records. Thus, assistance in using QRIS has proven to have a significant role in encouraging digital economic growth and financial inclusion at the local level.